2020
DOI: 10.12688/f1000research.26879.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined vitrectomy, near-confluent panretinal endolaser, bevacizumab and cyclophotocoagulation for neovascular glaucoma — a retrospective interventional case series

Abstract: Background: Neovascular glaucoma (NVG) is a severe, potentially blinding disease and a therapeutic challenge. The purpose of this study was to evaluate the safety and efficacy of an integrative surgical approach to neovascular glaucoma. Methods: Retrospective analysis of a one-year follow-up of a consecutive interventional case series of NVG. Eyes underwent transscleral cyclophotocoagulation, pars plana vitrectomy, near-confluent panretinal photocoagulation, and intravitreal bevacizumab. Phakic eyes underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…All 77 patients (45 male, 32 female, mean 73.6±12.2 years, range 29–91 years) completed a one-year follow-up and were included in the retrospective analysis ( Figure 1 ). Conditions that lead to NVG included CRVO 41.6% (32/77), PDR 35.1% (27/77), CRAO 19.5% (15/77), and ocular ischemic syndrome 3.9% (3/77) 37 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 77 patients (45 male, 32 female, mean 73.6±12.2 years, range 29–91 years) completed a one-year follow-up and were included in the retrospective analysis ( Figure 1 ). Conditions that lead to NVG included CRVO 41.6% (32/77), PDR 35.1% (27/77), CRAO 19.5% (15/77), and ocular ischemic syndrome 3.9% (3/77) 37 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Open Science Framework: Combined vitrectomy, near-confluent panretinal endolaser, bevacizumab and cyclophotocoagulation for neovascular glaucoma — a retrospective interventional case series. https://doi.org/10.17605/OSF.IO/QTCGV 37 .…”
Section: Data Availabilitymentioning
confidence: 99%
“…Due to VH, red blood cells from the posterior chamber can also block the trabecular meshwork resulting in ghost cell glaucoma, for which PPV becomes an important treatment strategy. Despite adequate PPV and endolaser PRP, these patients may require intravitreal anti-VEGF injections in the future due to nonresolving retinal/iris NV 151–153…”
Section: Managementmentioning
confidence: 99%
“…Bemerkenswert ist, dass in der Gruppe der Diodenlaser-Zyklophotokoagulation keine Phthisis bulbi auftrat, während 2 Patienten in der Gruppe mit dem Ahmed-Drainage-Implantat eine Phthisis entwickelten. Eine rezente Studie aus Würzburg zeigte günstige Ergebnisse für eine einmalige Operation mit einer Kombination aus einer transskleralen Diodenlaser-Zyklophotokoagulation (20 Herde), einer Pars-plana-Vitrektomie mit nahezu konfluenter Endolaserkoagulation von den Gefäßbogen bis zur Ora serrata und einer intravitrealen Bevacizumab-Eingabe 40 . Bei phaken Augen wurde zusätzlich eine Kataraktoperation durchgeführt.…”
Section: Neovaskularisationsglaukomeunclassified
“…It is worth noting that no phthisis bulbi occurred in the diode laser cyclophotocoagulation group, whereas two patients in the Ahmed drainage implant group developed this condition. A recent study from Würzburg showed favorable results for a single operation with a combination of transscleral diode laser cyclophotocoagulation (20 foci), pars plana vitrectomy with near-confluent endolaser coagulation from the vascular arches to the ora serrata, and intravitreal bevacizumab administration 40 . In phakic eyes, cataract surgery was also performed.…”
Section: Neovascular Glaucomamentioning
confidence: 99%